Effects of Health Care Payment Models on Physician Practice in the United States - Friedberg, Mark W. (RAND Corporation, 2015)
The project reported here aimed to describe the effects that alternative health care payment models have on physicians and physician practices in the United States. Project findings should help guide efforts to improve current and future alternative payment programs and help physician practices succeed in these new payment models. The report provides both findings and recommendations.